Effects of Dietary Alfalfa Meal Supplementation on the Growth Performance, Nutrient Apparent Digestibility, Serum Parameters, and Intestinal Microbiota of Raccoon Dogs (Nyctereutes procyonoides) - Xiaoli Chen; Xiao Li; Danyang Chen; Weigang Zhao; Xiuli Zhang; Weitao Yuan; Huazhe Si; Xuming Deng; Rui Du; Chao Xu (Animals, 2024)
The raccoon dog (Nyctereutes procyonoides) is a typical omnivore possessing wide dietary adaptability and tolerance to rough feeding, which may be attributed to its intestinal microbiota. The study aimed to investigate the effect of dietary alfalfa meal levels on the growth performance, nutrient apparent digestibility, serum parameters, and intestinal microbiota of raccoon dogs. Sixty raccoon dogs were randomly divided into four dietary treatments containing 0% (AM0), 5% (AM5), 10% (AM10), and 15% (AM15) alfalfa meal for a 60-day experiment. The results showed that compared to raccoon dogs fed the AM0 diet, those fed the AM5 and AM10 diets had no significant difference in growth performance, while those fed the AM15 diet experienced a significant decrease. Raccoon dogs fed the AM5 diet had no significant effect on the nutrient apparent digestibility. Dietary supplementation with alfalfa meal significantly decreased serum urea levels and increased the antioxidant capacity of raccoon dogs. The intestinal microbiome analysis showed that the richness and diversity of colonic microbiota significantly increased in the AM15 group. With the increase in dietary alfalfa meal levels, the relative abundance of fiber-degrading bacteria in the colon of raccoon dogs, such as Treponema, Phascolarctobacterium, and Christensenellaceae R-7 group, increased. However, the relative abundance of pathogenic bacteria, including Anaerobiospirillum, decreased. In conclusion, the inclusion of 5% alfalfa meal in the raccoon dogs’ diet had no effect on growth performance, but it exhibited the potential to improve serum antioxidant capacity and intestinal microbiota. This indicates that raccoon dogs have a certain tolerance to the addition of alfalfa meal in their diet.